ANALISIS PERAN RADIO DAN TELEVISI DALAM PENDIDIKAN KESEHATAN MASYARAKAT KOTA SEMARANG - Rahayu, Rini; Lestari, Lilik (Universitas Muhammadiyah Semarang, 2018)
The industrial revolution era 4.0 has led to the advancement of Smart Factories, Smart Industry, Industrial Internet of Things, and AdvancedManufacturing. The use of information technology has expanded in publichealth education. Electronic media in the form of radio and television arebelieved to be able to play a role in promoting health to the community, because they are able to foster healthy behavior. It is supported that radio has transformed its broadcast in the form of internet streaming audio, whiletelevision broadcasts can be played back on social media. Keywords: Radio, Television, Public Health Education